Dominican Republic : Implementing a Health Protection System that Leaves No One Behind - Rathe, Magdalena (World Bank, Washington, DC, 2018)
During the last 50 years, the Dominican Republic has experienced important economic growth, with rates higher than most Latin American countries. However, despite the substantial reduction in poverty and indigence in recent years, average wages within the formal sector remain extremely low, and a large proportion of the working-age population is outside the formal sector. The country introduced a structural health reform in 2001, which has been successful in affiliating 70 percent of the population to the Family Health Insurance, with a complete package of services with the same content for all, although with different forms of financing and provision of services. However, the public service network, which is legally in charge of providing care to the lower-income population, lagged in its restructuring process, with serious problems of quality, efficiency, and governance. Thus, although many of the coverage goals have been achieved, population health outcome indicators remain well behind most countries in the Latin America region. Another key aspect of the pending agenda to achieve greater health and financial protection within social insurance is the in-depth revision of the Basic Health Plan (Plan Básico de Salud). This revision’s objective would be built on guaranteed coverage of certain health conditions considered to be priorities, including the restructuring of the health care model to introduce rationality, control costs, reduce or eliminate funding differences between the Contributory Regime (Regimen Contributivo) and Subsidized Regime (Régimen Subsidiado), and increase public funding for the Subsidized Regime. It is necessary to ensure that the benefits provided in the Basic Health Plan are delivered; that is, that the services required by the population are effectively covered, which will also reduce out-of-pocket spending. It is necessary to monitor the financial situation of all entities of the health system and to continue strengthening institutional capacity to carry out the financial and technical audits of health providers. The permanent monitoring of the financial sustainability of the Family Health Insurance Subsidized Regime and the Basic Health Plan is fundamental, while a systematic analysis of the fiscal space is carried out.